2015
DOI: 10.1080/13102818.2015.1095654
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of bioactive components in pear genotypes from Ardahan/Turkey

Abstract: In this study, 10 pear genotypes ( _ Incir, Bal, Nene, Kabak, Banda, Kırmızı, _ Imlahor, Baraka, Limon and G€ u g€ um), which grow in the Ardahan region, were evaluated for their total phenolic content, total anthocyanin content, brix , pH, titratable acidity, total ascorbic acid content and antioxidant activity. According to the results, the pear genotypes used in this study had a high brix8 content, high phenolic, anthocyanin and ascorbic acid contents, as well as high antioxidant activity. It was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 59 publications
1
13
1
2
Order By: Relevance
“…However, in pear, total phenolic content (150.33 0.16mg/100g) were observed. The results were in conformity with the findings of Abaci et al (2015) [1] . Reducing sugars (%) 4.12 ±0.20 6.…”
Section: Physico-chemical Characteristicssupporting
confidence: 93%
“…However, in pear, total phenolic content (150.33 0.16mg/100g) were observed. The results were in conformity with the findings of Abaci et al (2015) [1] . Reducing sugars (%) 4.12 ±0.20 6.…”
Section: Physico-chemical Characteristicssupporting
confidence: 93%
“…85.95±0.1 mg/l, 600±0.01 mg GAE/l, IC 50 value 250±0.00 mg of phenol/l, and 12.2±0.01 mg/100 ml respectively. Compared to a previous similar research [23], where the level of tannin was observed to be 1.6 g/l, this study, found the level of tannin in Yakumo pear equal to 0.93±0.01 g/l [24]. Anthocyanins are responsible for the red coloration in pear fruits and its development depends on heat and light.…”
Section: Discussioncontrasting
confidence: 73%
“…The total phenolics content of the clones ranged from 72.61 mg 100 g −1 (A-11) to 147.38 mg 100 g −1 (A-19). In related studies, the total phenolics content were reported between the ranges 307.06-717.08 mg 100 g −1 for pear genotypes grown in Bosnia and Herzegovina (Duric et al, 2015), 8-140 mg 100 g −1 for pear genetic resources in Northern Japan (Ieguchi et al, 2015), 112.6-230.5 mg 100 g −1 for local pear variety grown in Ardahan (Abacı et al, 2016), 126.1-215.2 mg 100 g −1 for local pear variety grown in Posof (Erbil et al, 2018), 9.88-22.09 mg 100 g −1 for pear genetic resources in Italy (Azzini et al, 2019), 15.17-190.46 mg 100 g −1 for pear variety grown in Northeast Bosnia (Salkic et al, 2019). Findings regarding the total phenolic content showed differences rather than partial similarities with those of pear genetic resources from different countries and growing ecologies.…”
Section: Resultsmentioning
confidence: 99%
“…Pear is also rich in terms of phenolic compounds and antioxidant promoting human health (Li et al, 2016;Yim and Nam, 2016). Studies to determine the bioactive properties of pear genetic resources are limited (Duric et al, 2015;Abacı et al, 2016;Azzini et al, 2019). Pear genetic resources with high antioxidant capacity are important for breeding materials (Ieguchi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%